Instrument development on measuring Malaysian households’ intention to practise solid waste segregation-at-source - Cheng, Kai Wah; Osman, Syuhaily; Md Jusoh, Zuroni; Leby, Jasmine Lau (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The grade of the environment is gradually declining especially when it comes to the severe problem of solid waste. It has become a challenging burden for many large metropolitan heterogeneous areas in most of the developing countries. The main purpose of this research is to investigate the relationship between households’ attitude, descriptive norm and injunctive norm with intention to practise solid waste segregation-at-source and to ascertain the mediating effect of environmental concern and moderating effect of environmental knowledge between households’ attitude, descriptive norm and injunctive norm with intention to practise solid waste segregation-at-source. The instrument is then validated from four main aspects: face validity, content validity, convergent validity and discriminant validity. After the validation process, the pre-test of this research instrument is conducted among 30 Malaysian households. All the statements have been adjusted after reliability and validity test. The final version of the instrument is set in both closed and open format which consists of eight sections: respondent’s particulars (11 items), general questions on solid waste segregation-at-source (7 items), attitude (14 items), descriptive norm (12 items), injunctive norm (12 items), environmental concern (three subparts and 12 items), environmental knowledge (25 items) and intention to practise solid waste segregation-at-source (8 items). The instrument can further be used to examine other similar research areas such as sustainable consumption, recycling as well as solid waste management.